Secure Turbo Codes Design Using Chaotic Interleaver Based on Generalized 2D Chaotic Map - Ahmed Sahnoune; Chellali, Sefouane; Berkani, Daoud; Zeraoulia, Elhadj (Automatic control and computer sciences, 2024)
Design of interleavers with a compromise between reliability and complexity of implementation is a challenging code design problem. This paper deals with the design of chaotic interleavers for secure turbo codes using a novel generalized 2D chaotic map. Compared with random interleavers, the proposed interleavers improve the performances while reducing the complexity of implementation. Furtheremore, parameters of chaotic maps can be used to jump from a map to the other which improve the security against decoding attacks. The proposed interleavers enhance the reliability and physical layer security.